PENGARUH KEDISIPLINAN TERHADAP PENINGKATAN PRESTASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PKN DI SMK PASUNDAN 1 SUBANG - Cahyono, Cahyono (STKIP Subang, 2016)
Discipline is berperanguh to increased student achievement. This study aims to collect information on students' disciplinary effect on student achievement in the subjects of Civics at SMK Pasundan 1 Subang. Using the theory of discipline (Maman Rachman and A. Kosasih Djahiri) and the theory of learning achievement (Moh. Surya). By using a quantitative approach. Penenlitian sample as many as 108 students and 2 teachers Civics. The results showed that the discipline of the students have a significant influence on the improvement of student achievement that is, True 0, 832. It can be concluded that the higher discipline learners, it will be a good learning achievements of learners, especially on the subjects PPKn in SMK Pasundan 1 Subang